2017
DOI: 10.12659/msm.900667
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MiR-146a and TRAF6 in the Diagnose of Lupus Nephritis

Abstract: BackgroundLupus nephritis (LN) is a major complication of systemic lupus erythematosus (SLE). This study tested miR-146a and its target gene TRAF6 expression in LN patients and discussed their relationship with LN.Material/MethodsOne hundred twenty-eight LN patients and 30 healthy controls were enrolled in this study. MiR-146a and TRAF6 expression in peripheral blood mononuclear cells (PBMCs) were detected. Serum cytokines content was determined by ELISA. The diagnostic role of miR-146a and TRAF6 in LN activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…However, five articles were excluded by reading their complete articles due to article types, seven studies lacked available data to construct a 2×2 table, and four articles lacked a comparison between SLE patients and healthy controls. Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, five articles were excluded by reading their complete articles due to article types, seven studies lacked available data to construct a 2×2 table, and four articles lacked a comparison between SLE patients and healthy controls. Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials.…”
Section: Search Resultsmentioning
confidence: 99%
“…Additionally, the ideal time for specimen acquisition was before treatment. Unfortunately, only two of the studies [17,31] involved in our meta-analysis indicated that blood samples were collected before treatment, while six studies [20,33,37,39,40,42] did not clarify when the specimens were obtained, five studies [18,19,21,36,41] stated that samples were collected during the period of treatments, and four articles [32,34,35,38] indicated that the time for specimen collection was after the patients had stopped treatments for a period of time. Thus, these differences in patient and blood collection time could cause inevitable bias to our results.…”
Section: Discussionmentioning
confidence: 99%
“…The level of miR-146a was obviously downregulated in the PBMCs of SLE patients, and it could restrain the expression and secretion of IL-1 β , IL-6, IL-8, and TNF- α [32]. It negatively regulated NF- κ B signaling pathway and inflammatory reaction activation through targeting TRAF6 [33]. In this study, we observed that serum exosomal miR-146a was decreased in 10 SLE patients in a miRNA level.…”
Section: Discussionmentioning
confidence: 85%
“…TRAF6 is positively correlated with serum IL-1 β , IL-6, IL-8, and TNF- α activities. miR-146a reduction and TRAF6 upregulation increase the likelihood of the progression and recurrence of end-stage renal disease (ESRD) within one year [ 97 ]. Interestingly, miR-146a is enriched in urinary exosomes in patients with LN [ 98 ].…”
Section: The Role Of Traf6 In Autoimmune Diseasesmentioning
confidence: 99%